2001
DOI: 10.1111/1467-9507.00145
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and Gender Differences in Task and Social Interpretations of Peer Collaborative Problem Solving

Abstract: Investigations of peer collaboration often vary task or social aspects of collaborative contexts and assume that these aspects of the context are experienced similarly by individuals. The present study examined how social aspects (group friendship and gender) of a peer collaborative context related to differences in adolescents' interpretations of task and social problems that occurred while collaborating with peers in a naturalistic classroom setting. Eighth-grade adolescents (N = 82, 44 females) worked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Many students prefer to work with friends, and may be more likely to disagree and to work through disagreements (Azmitia & Montgomery, 1993;Strough, Berg, & Meegan, 2001;Zajac & Hartup, 1997).…”
Section: Ideas and Identities 25mentioning
confidence: 99%
“…Many students prefer to work with friends, and may be more likely to disagree and to work through disagreements (Azmitia & Montgomery, 1993;Strough, Berg, & Meegan, 2001;Zajac & Hartup, 1997).…”
Section: Ideas and Identities 25mentioning
confidence: 99%
“…On this binary view, nonfriend dyads include both pairs that do not know each other and pairs that do not like each other. By aggregating these two distinct cases, it has been suggested that the "friend" condition fares more favorably than if it were compared simply against pairs who did not know each other (Strough, Berg, & Meegan, 2001). An additional factor to consider is that pairs may not rate each other symmetrically.…”
Section: Prior Research On Collaboration Among Friendsmentioning
confidence: 99%
“…Vygotskian sociocultural theory predicts that collaboration leads to cognitive growth when partners arrive at a shared or intersubjective understanding of the situation (Bearison, Magzamen, & Filardo, 1986;Gauvain & Rogoff, 1989;Glassman, 1994;Hartup, 1996a;Russell, 1982;Tudge, 1992;Tudge, Winterhoff, & Hogan, 1996). Researchers have begun to address whether friendship of partners is associated with the development of a shared understanding of tasks and performance on such tasks (Azmitia & Montgomery, 1993;Strough, Berg, & Meegan, 2001;Strough & Cheng, 2000;Strough, Swenson, & Cheng, 2001). This focus on friendship comes from research indicating that having a friend is beneficial to adjustment in general (Demir & Urberg, 2004;Dunn, 2004;Hartup, 1996b;Hartup & Stevens, 1997;Ladd & Kochenderfer, 1996).…”
Section: Vygotskian Theory and Peer Collaborationmentioning
confidence: 99%